The myth of the team captain as principal leader: extending the athlete leadership classification within sport teams - Fransen, K.; Vanbeselaere, N.; de Cuyper, B.; vande Broek, G.; Boen, F. (Journal of Sports Sciences, 2014)
Although coaches and players recognise the importance of leaders within the team, research on athlete leadership is sparse. The present study expands knowledge of athlete leadership by extending the current leadership classification and exploring the importance of the team captain as formal leader of the team. An online survey was completed by 4,451 participants (31% females and 69% males) within nine different team sports in Flanders (Belgium). Players (N = 3,193) and coaches (N = 1,258) participated on all different levels in their sports. Results revealed that the proposed additional role of motivational leader was perceived as clearly distinct from the already established roles (task, social and external leader). Furthermore, almost half of the participants (44%) did not perceive their captain as the principal leader on any of the four roles. These findings underline the fact that the leadership qualities attributed to the captain as the team`s formal leader are overrated. It can be concluded that leadership is spread throughout the team; informal leaders rather than the captain take the lead, both on and off the field.